(3GdchGcH GdOQjI aj JQGLe GdSGOI GdUhajIs - (3eMeO YHO GdQDha Hf JGL GdYGQajf GHf Ydj Hf Rjf GdYGHOjf GdMOGOj Ke GdefGhj GdbGgQj, Rjf GdOjf,J (B1031 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Sbi ChdjGAg hCYGXe YHGOg ef cCS hOGOg s
(3QJHg Ydi CMO YTQ WHbIs
(3hLYd cd WHbI eGFI SfIs
(3hQJH cd WHbI Ydi MQha GdeYLes
(3fSNI NRGFfjI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdJGQjNs